Physics and metaphysics of nuclear particles and antiparticles - Yar-Mukhamedova, Г.Ш.; Mukashev, Қ.; Gabdrakhmanova, Л.А.; Umarov, Ф.Ф. (Recent Contributions to Physics, 2025)
The paper describes a hypothetical model of the interaction of particles and antiparticles using the example of a positron and an electron by assuming a change in their state of physical without involving theoretical calculations, which most often represent fitting data to the desired results. Since these two particles belong to the class of leptons, both weak and electromagnetic interactions are possible between them. Weak interactions by the nature of the manifestation are short-range, and electromagnetic interactions are long-range. In a solid between differently charged particles, both of these interactions can exist simultaneously to ensure their mutual attraction. But the nature and mechanism of these interactions has still not been clarified to the end. In this regard, a hypothetical model of the honeycomb structure of the positron and electron is woven from even smaller - femto- or actor-sized particles in the form of «positronites» and «electronities» that perceive radiation from the opposite side by changing their state of aggregation. Subsequently, this model develops into a model of the capture of positrons by defects in the crystal structure of solids.